How to Get the Biggest Slice of the Cake. A Comparative View of Social Behaviour and Resource Access in Human Children and Nonhuman Primates - Vermande, Marjolijn M.; Sterck, Elisabeth H. M. (Frontiers in Psychology, 2020)
Social complexity results from engaging in different classes of social behaviour. The presence of different classes of social behaviour is reflected in multidimensional concepts of social asymmetry, found in both human and nonhuman primates. Based on an overview of such concepts, we propose that three classes of social behaviour are involved in having access to scarce and desired resources: Next to aggressive and affiliative behaviour, also action indicating behaviour (i.e., inspire another individual to follow one’s example or intentions) may lead to resource access. Studies with nonhuman primate and human children show that the contribution of aggression and affiliation to resource access has been widely documented and that there is initial support for action indicating behaviour. In addition, the studies show similarities and differences in conceptualization and approach that may inspire future research. Future research should address the (in)dependency of the behavioural dimensions, their relative importance, individual differences in combined expression and the type of resources accessed. Only a multi-dimensional view on behaviour leading to resource access will highlight the benefits of social complexity.